Insulin-like growth factor binding protein 5b of Trachinotus ovatus and its heparin-binding motif play a critical role in host antibacterial immune responses via NF-κB pathway - Du, Hehe; Zhou, Yongcan; Du, Xiangyu; Zhang, Panpan; Cao, Zhenjie; Sun, Yun (Frontiers in Immunology, 2023)
Introduction Insulin-like growth factor binding protein 5 (IGFBP5) exerts an essential biological role in many processes, including apoptosis, cellular differentiation, growth, and immune responses. However, compared to mammalians, our knowledge of IGFBP5 in teleosts remains limited. Methods In this study, TroIGFBP5b, an IGFBP5 homologue from golden pompano (Trachinotus ovatus) was identified. Quantitative real-time PCR (qRT-PCR) was used to check its mRNA expression level in healthy condition and after stimulation. In vivo overexpression and RNAi knockdown method were performed to evaluate the antibacterial profile. We constructed a mutant in which HBM was deleted to better understand the mechanism of its role in antibacterial immunity. Subcellular localization and nuclear translocation were verified by immunoblotting. Further, proliferation of head kidney lymphocytes (HKLs) and phagocytic activity of head kidney macrophages (HKMs) were detected through CCK-8 assay and flow cytometry. Immunofluorescence microscopy assay (IFA) and dual luciferase reporter (DLR) assay were used to evaluate the activity in nuclear factor-κB (NF-κβ) pathway. Results The TroIGFBP5b mRNA expression level was upregulated after bacterial stimulation. In vivo, TroIGFBP5b overexpression significantly improved the antibacterial immunity of fish. In contrast, TroIGFBP5b knockdown significantly decreased this ability. Subcellular localization results showed that TroIGFBP5b and TroIGFBP5b-δHBM were both present in the cytoplasm of GPS cells. After stimulation, TroIGFBP5b-δHBM lost the ability to transfer from the cytoplasm to the nucleus. In addition, rTroIGFBP5b promoted the proliferation of HKLs and phagocytosis of HKMs, whereas rTroIGFBP5b-δHBM, suppressed these facilitation effects. Moreover, the in vivo antibacterial ability of TroIGFBP5b was suppressed and the effects of promoting expression of proinflammatory cytokines in immune tissues were nearly lost after HBM deletion. Furthermore, TroIGFBP5b induced NF-κβ promoter activity and promoted nuclear translocation of p65, while these effects were inhibited when the HBM was deleted. Discussion Taken together, our results suggest that TroIGFBP5b plays an important role in golden pompano antibacterial immunity and activation of the NF-κβ signalling pathway, providing the first evidence that the HBM of TroIGFBP5b plays a critical role in these processes in teleosts.